2009
DOI: 10.1038/npp.2009.26
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-Concept Trial with the Neurosteroid Pregnenolone Targeting Cognitive and Negative Symptoms in Schizophrenia

Abstract: The neurosteroid pregnenolone and its sulfated derivative enhance learning and memory in rodents. Pregnenolone sulfate also positively modulates NMDA receptors and could thus ameliorate hypothesized NMDA receptor hypofunction in schizophrenia. Furthermore, clozapine increases pregnenolone in rodent hippocampus, possibly contributing to its superior efficacy. We therefore investigated adjunctive pregnenolone for cognitive and negative symptoms in patients with schizophrenia or schizoaffective disorder receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
158
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(167 citation statements)
references
References 140 publications
8
158
0
Order By: Relevance
“…The several-fold increases in pregnenolone and allopregnanolone levels posttreatment are consistent with findings in a previous study that administered pregnenolone (500 mg/day) for 8 weeks to patients with schizophrenia (Marx et al, 2009). In addition, pregNANolone levels also increased several-fold posttreatment.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The several-fold increases in pregnenolone and allopregnanolone levels posttreatment are consistent with findings in a previous study that administered pregnenolone (500 mg/day) for 8 weeks to patients with schizophrenia (Marx et al, 2009). In addition, pregNANolone levels also increased several-fold posttreatment.…”
Section: Discussionsupporting
confidence: 79%
“…More recent work has suggested that pregnenolone and its metabolites modulate functional connectivity in the human amygdala (Sripada et al, 2014) and enhance activation of neurocircuits pertinent to mood and emotions (Sripada et al, 2013). Clinical trials suggest that pregnenolone and its derivatives, such as allopregnanolone, have potential in treating schizophrenia (Marx et al, 2009;Ritsner et al, 2010;Zorumski et al, 2013b). However, the sample sizes in these studies have been small.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In a broader sense, a better explication of hormonal effects on neural circuits may not only reveal mechanisms of risk for women but can inform our understanding of the relevant disorders more generally. As one example, activation of the prefrontal cortex during a working memory task is dependent on gonadal steroid stimulation, providing a potential approach to one of the fundamental deficits in schizophrenia (Berman et al 1997;Marx et al 2009). …”
Section: Manual Of Mental Disorders (Dsm)-v and Internationalmentioning
confidence: 99%